Compulsory Citizenship Behavior and Its Outcomes: Two Mediation Models - Liang, Huai-Liang; Yeh, Tsung-Kai; Wang, Chia-Hsuan (Frontiers in Psychology, 2022)
Employees view compulsory citizenship behavior (CCB) as concessionary behavior they undertake because of pressure exerted by their organizations. This study applies affective events theory to CCB－workplace deviance relationships, and impression management theory to CCB－facades of conformity relationships, to posit that employee emotional exhaustion is an essential mediating factor that effectively explains how CCB contributes to workplace deviance and facades of conformity. This study utilizes two mediation models to investigate whether employees’ CCBs are positively related to their work deviance and false behavior, and how emotional exhaustion mediates those relationships. Two-wave data collected from 655 valid participants (480 males, 175 females; average age of 30.1 years) in a public sector bank and a large private bank in Taiwan supported our hypotheses. We conducted surveys with volunteer employees that included CCB, emotional exhaustion, facades of conformity, and work deviance. The results of this study uncovered statistically significant relationships between CCB and work deviance and between CCB and facades of conformity and revealed that emotional exhaustion significantly mediated these relationships. Implications and directions for future study are discussed.